Influence humidity of wood on the process gasification of wood in a continuous layer - Лис, Степан Степанович; Мисак, Йосиф Степанович (Eastern-European Journal of Enterprise Technologies, 2012)
This paper presents the results of research of the influence humidity of wood on the process thermal recycling of wood in a continuous layer to the gaseous fuel. We obtain the regression equation, which can be the basis for the process under investigation and rational control